2019
DOI: 10.1101/2019.12.25.888412
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal interference stimulation targets deep brain regions by modulating neural oscillations

Abstract: Temporal interference (TI) stimulation of the brain generates amplitude-modulated electric fields oscillating in the kHz range. A validated current-flow model of the human head estimates that amplitude-modulated electric fields are stronger in deep brain regions, while unmodulated electric fields are maximal at the cortical regions. The electric field threshold to modulate carbacholinduced gamma oscillations in rat hippocampal slices was determined for unmodulated 0.05-2 kHz sine waveforms, and 5 Hz amplitude-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…It may be possible to obtain these subthreshold fields strengths with TI stimulation and to direct TI fields toward specific deep brain regions by utilizing specific electrode montages, electrode sizes, and multiple waveforms (Cao and Grover, 2020;Howell and McIntyre, 2020;Huang and Parra, 2019;Rampersad et al, 2019). It may also be possible to exploit cellular or network features that are specific to certain brain regions (Esmaeilpour et al, 2019) to maximize the subthreshold effects of TI stimulation. Moreover, the potential effects of transcutaneous stimulation, including TI, may not be limited to neurons.…”
Section: Articlementioning
confidence: 99%
“…It may be possible to obtain these subthreshold fields strengths with TI stimulation and to direct TI fields toward specific deep brain regions by utilizing specific electrode montages, electrode sizes, and multiple waveforms (Cao and Grover, 2020;Howell and McIntyre, 2020;Huang and Parra, 2019;Rampersad et al, 2019). It may also be possible to exploit cellular or network features that are specific to certain brain regions (Esmaeilpour et al, 2019) to maximize the subthreshold effects of TI stimulation. Moreover, the potential effects of transcutaneous stimulation, including TI, may not be limited to neurons.…”
Section: Articlementioning
confidence: 99%
“…These should be examined rigorously, especially for prospective clinical use. Some previous studies have explored the high-frequency conduction block biophysics of TI stimulation (Mirzakhalili et al, 2020 ), while others have investigated the membrane characteristics in hippocampal gamma oscillations attributed to interfering stimulation (Esmaeilpour et al, 2021 ). In our simulation, the envelope frequency was determined as 10 Hz, which is a suitable choice for both computational and experimental study (Grossman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our simulation, the envelope frequency was determined as 10 Hz, which is a suitable choice for both computational and experimental study (Grossman et al, 2017 ). However, this modulation frequency should also be determined according to the anticipated clinical effects, for example, 5Hz, to modulate the gamma oscillation (Esmaeilpour et al, 2021 ). Therefore, future work could focus on the investigation of the mechanisms of brain activation in response to TI neuronal stimulation in both animal models and realistic clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…To model TI-stimulation, it was found that IF-neurons are not sufficient to reproduce the experimental behaviour on single neuron level [16]. However, when IF-neurons are placed in a network and GABA b postsynaptic inhibition is included, the computational results were in line with experimental observations of TI-stimulation [17]. Furhter on, for single cell neurons, it is possible to have neurons exhibiting TI-stimulation when using the FitzHugh-Nagamo model and the Hodgkin-Huxley model.…”
Section: Introductionmentioning
confidence: 92%